Exponentiation, Modular Multiplication and VLSI Implementation of High-Speed RSA Cryptography - Orup, Holger (DAIMI Report Series, 1995)
This Ph.D. thesis treats the calculation of modular exponentials using very large operands. Through a top-down approach, the basic operations are identified: modular multiplication, modular addition, addition, modular reduction, and quotient determination. Various methods and optimisation techniques for these operations are decribed and compared. The focus is directed toward methods that are suited for VLSI implementation. A very fast VLSI processor has been designed, constructed, and tested.